COMPARISON OF GCS VS MOTOR COMPONENT ALONE AS AN EFFECTIVE PREDICTOR IN SEVERE HEAD TRAUMA TRIAGE. : J Peop Univ Med Health Sci. 2025:15(3), 71-79. http://doi.org/10.46536/jpumhs/2025/15.03.660 - Syed Ali Anwar1, Inayat Ali Khan2, Fareha Mansoor Khan3, Asif Nawaz4, Muhammad Uzair5, khalid Khan6. (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Severe head trauma is a leading cause of disability and mortality worldwide, particularly among young adults, and imposes a substantial burden on healthcare systems. OBJECTIVES: This study aims to compare the accuracy of the total GCS (GCSt) versus the GCS motor component (GCSm) alone in triaging patients with head trauma. METHODS: This six-month longitudinal study was conducted in the Emergency Department of Ziauddin University Hospital, Karachi, enrolling 127 head trauma patients (aged 18–60) via consecutive sampling. Those with ischemic stroke, GCS score of 3, polytrauma, spinal trauma, and prior neurologic conditions were excluded. Background information, vitals and trauma details were recorded, and each patient was assessed using both GCSt and GCSm. Diagnostic accuracy measures sensitivity, specificity, PPV, NPV, and ROC curves were calculated. RESULTS: The mean patient age was 43.0 ± 13.0 years; 65.35% were male. Road traffic accidents were the leading cause of head injury, followed by falls. For severe cases; the GCSm demonstrated perfect diagnostic performance with 100% sensitivity, specificity, PPV, NPV, and overall accuracy. In moderate cases, GCSm showed 91.38% sensitivity, 100% specificity, and 96.88% accuracy, with only two false negatives. For mild cases, GCSm achieved 100% sensitivity, 96.55% specificity, and 98.35% accuracy. ROC analysis showed excellent discriminative ability for both GCSt (AUC 0.916; 95% CI: 0.866–0.966) and GCSm (AUC 0.914; 95% CI: 0.862–0.965), both p<0.001. GCSm consistently demonstrated high diagnostic accuracy across all injury severities and mechanisms, including RTAs and falls CONCLUSION: The GCS motor component showed high diagnostic accuracy across head trauma severities, closely aligning with total GCS performance, and demonstrated near-perfect sensitivity and specificity in mild and severe cases. Its simplicity and reliability make GCSm a strong, efficient alternative for routine triage in emergency care.